Análise da mudança de turno de operação em uma mina a céu aberto - estudo de caso - Bárbara Cardoso Avelar (2023)
The shift regime directly impacts the performance of the Mine Operations because it has a direct influence on the physical use of equipment. Furthermore, there are risk factors for the health and safety of workers associated with the chosen system, such as: alteration of biological rhythms, effects on the family and social quality of life, psychological effects, and influence on the accident rate in mining operations. The present work seeks to analyze the change in the duration of the Mine Operation shift in an open-pit mine, in order to compare the 6 hour shift and 11 hour shift, with regard to: physical use of transport fleets, number of days off and working days for operators, infrastructure dedicated to the operational team, available safety tools, type of shift (fixed and alternate), and operational time (continuous and total). The results indicate a theoretical gain (without external influences) of 5% in the physical use of equipment with the 11-hour shift compared to the 6-hour shift. A practical comparison between the regimes was also carried out, and the results indicated an increase of an average of 3.7% in the physical use of equipment while the 11-hour shift was applied compared to the period that the 6-hour shift was applied. It is important to mention that external factors such as the addition of 5 trucks in the first half of 2023, followed by the delay in mobilizing transport operators, made the analysis difficult. Therefore, it was necessary to analyze the physical use of equipment reasons influenced by the change in shift regime singly, such as shift change, operator lecture, meal and snack, ergonomic break and operator change. Finally, according to a survey carried out with 87% of the operator public, 87% were satisfied with the new shift, while 8% were indifferent to the change, and 5% were dissatisfied with the change. Furthermore, the operators who responded to the survey indicated that having more time with family and friends was the biggest gain from implementing the 11am shift.